2017
DOI: 10.3390/met7060207
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Reclamation of Strategic and Energy Critical Metals from Secondary Resources

Abstract: Abstract:Metals with an average crustal abundance of <0.01 ppm, which are high in supply shortage due to soaring demand, can, under the excessive environmental risk and <1% recycling rate of their production, be termed as 'critical' in a limited geo-boundary. A global trend to the green energy and low carbon technologies with geopolitical scenario is challenging for the sustainable reclamation of these metals from secondary resources. Among the available processes, bio-reclamation can be a sustainable techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 101 publications
1
22
0
Order By: Relevance
“…The following papers focused on the improvement of valuable metal recycling processes through enhanced process efficiency. Ilyas et al [4] summarized methods of bio-recovery from secondary resources for strategic and energy critical metals, such as rare earth elements, precious metals, and a common nuclear fuel element; they also suggested that sustainable recycling could be achieved by means of bio-metallurgy. Reyes-Valderrama et al [5] performed a voltammetry study for the recovery of Cu, Zn, and Ni from an e-waste leach solution to understand the behaviors of leaching and electrodeposition; they also reported selective electro-deposition with different pHs.…”
Section: Selective Extraction Of Valuable Metals From Wastsmentioning
confidence: 99%
“…The following papers focused on the improvement of valuable metal recycling processes through enhanced process efficiency. Ilyas et al [4] summarized methods of bio-recovery from secondary resources for strategic and energy critical metals, such as rare earth elements, precious metals, and a common nuclear fuel element; they also suggested that sustainable recycling could be achieved by means of bio-metallurgy. Reyes-Valderrama et al [5] performed a voltammetry study for the recovery of Cu, Zn, and Ni from an e-waste leach solution to understand the behaviors of leaching and electrodeposition; they also reported selective electro-deposition with different pHs.…”
Section: Selective Extraction Of Valuable Metals From Wastsmentioning
confidence: 99%
“…The mechanism of thiosulfate and polysulfides taking place in the extraction of metal values from their sulfides is presented in Fig. . Heterotrophic biological agents (bacteria or, fungi) are able to produce organic metabolic end products that can solubilize metals from carbonates, phosphate, silicates or flouride containing minerals by chelation, oxidation–reduction and acid dissolution.…”
Section: Metal‐microbes Interaction and Integration With Chemical Promentioning
confidence: 99%
“…Depletion of primary reserves of metals has shown unprecedented growth in the recycling of metals from divergent secondary/spent/waste materials, which have also been explored with the aid of bio‐chemical processing in recent years . Useful research carried out in this direction is summarized in Table .…”
Section: Hybrid Bio‐chemical Processingmentioning
confidence: 99%
See 2 more Smart Citations